Investigation of Pharmacokinetic Parameters of Trelagliptin in Egyptian Volunteers Using Sensitive LC-MS/MS: A Comparative Study with a Japanese Population - Shereen Mowaka; Nermeen Ashoush; Mariam M. Tadros; Bassam M. Ayoub (Journal of Analytical Methods in Chemistry)
Trelagliptin (TLN) is a novel once-weekly antidiabetic drug that enhanced the patient compliance in type 2 diabetes. TLN analysis and bioanalysis literature review showed many methods for TLN assay either in dosage form or as biological fluids (pharmacokinetic parameters), but all those methods did not consider the full details dealing with biological assay of TLN. Studies that included information about pharmacokinetic parameters did not mention the used analytical procedures for those determinations and parameters. Although some LC-MS/MS and UPLC-UV methods were reported for TLN bioassay in rats’ plasma, they used direct precipitation techniques, and the current described procedure showed lower LLOQ than all the reported methods in spite of that working on human plasma is more complicated than on rats’ plasma. In this study, LC-MS/MS bioanalysis of TLN in human plasma (4–1000 nM) was employed successfully with LLOQ of 4 nM which is lower than all reported methods in rats’ plasma followed by a preliminary pharmacokinetic study. Alogliptin was used as internal standard (IS) because of its structure similarity to TLN. Pharmacokinetic parameters of TLN were investigated in Egyptian volunteers, and they had been compared to Japanese. Liquid-liquid extraction showed more sensitive results than direct precipitation. The proposed method was successfully applied to a pharmacokinetic study conducted on Egyptian volunteers. No dose modification is required upon comparing the pharmacokinetic parameters of the current study and previous studies on non-Egyptian volunteers.